Dual roles of misshapen/NIK-related kinase (MINK1) in osteoarthritis subtypes through the activation of TGFβ signaling. Issue 1 (January 2020) - Yu, D.; Hu, J.; Sheng, Z.; Fu, G.; Wang, Y.; Chen, Y.; Pan, Z.; Zhang, X.; Wu, Y.; Sun, H.; Dai, J.; Lu, L.; et al.
Summary: Objective: To identify the role of misshapen/NIK-related kinase (MINK1) in age-related Osteoarthritis (OA) and injury-induced OA, and the effects of enhanced TGFβ signaling in these progresses. Design: The effect of MINK1 was analyzed with MINK1 knock out ( Mink1−/− ) mice and C57BL/6J mice. OA progress was studied in age-related OA and instability-associated OA (destabilization of the medial meniscus, DMM) models. The murine knee joint was evaluated through histological staining, Osteoarthritis Research Society International (OARSI) scores, immunohistochemistry, and μCT analysis. Primary chondrocytes were isolated from wild type and Mink1−/− mice and subjected to osteogenic induction and Western blot analysis. Results: MINK1 is highly expressed during cartilage development and in normal cartilage. Mink1−/− mice displayed markedly lower OARSI scores, aggrecan degradation neoepitope positive cells and increased Safranin O and pSMAD2 staining in aging-related OA model. However, in injury-induced OA, loss of MINK1 accelerates extracellular matrix (ECM) destruction, osteophyte formation, and subchondral bone sclerosis. Accelerated subchondral bone remodeling in Mink1−/− mice was accompanied with increased numbers of nestin-positive mesenchymal stem cells (MSCs) and osterix-positive osteoprogenitors. pSMAD2 staining was increased in the subchondral bone marrow of Mink1−/− mice and overexpression of MINK1 inhibited SMAD2 phosphorylation in vitro . Conclusions: This study shows for the first time that activation of TGFβ/SMAD2 by MINK1 deficiency plays opposite roles in aging-related and injury-induced OA. MINK1 deficiency protects cartilage from degeneration in aging joints through increased SMAD2 activation in chondrocytes, while accelerating OA progress in injury-induced model through enhanced osteogenesis of MSCs in the subchondral bone. These findings provide insights for developing precision OA therapeutics targeting TGFβ/SMAD2 signaling.